Circular RNA circCCDC66 Contributes to Malignant Phenotype of Osteosarcoma by Sponging miR-338-3p to Upregulate the Expression of PTP1B. (11th August 2020) - Xiang, Deng; Li, Yugang; Lin, Yanshui
Abstract : In recent years, the mechanism of cancer research has become hotspots of life science and medicine, especially due to the rapid development of molecular medicine and bioinformatics research. Similarly, the molecular mechanism also has received increasing attention in osteosarcoma (OS) research. Also, a considerable amount of research confirmed that circular RNAs (circRNAs) could regulate cancer cell growth and metastasis. This study aimed to explore the effect of a circRNA, circCCDC66, on OS and reveal its potential molecular mechanism. High circCCDC66 expression level was found in OS patient-derived tissue samples and OS cell lines by qRT-PCR. The abilities cell proliferation and metastatic of U2OS and SW1353 cells were then assessed by Cell Counting Kit-8 and transwell assay, respectively. The interaction between circCCDC66 and its target miRNAs were verified by the dual-luciferase reporter assay. Through functional experiments, we found that circCCDC66 knockdown promoted the inhibition of cell proliferation and metastatic of OS cell lines. From mechanistic perspective, circCCDC66 upregulated PTP1B by sponging miR-338-3p. Collectively, our findings demonstrated that circCCDC66 contributed to malignant behaviors of OS cells by miR-338-3p/PTP1B pathway, which suggested circCCDC66/miR-338-3p/PTP1B axis might be a potential therapeutic target.